Intellectual property rights (IPRS) and economic development - Md. Zafar Mahfooz Nomani,Ed; Faizanur Rahman,Ed (New Century, 2018)
Globalization and the rapid proliferation of technology have elevated the significance of intellectual property protection. The importance of IPRs has increased in recent years in the wake of rapid advancements and proliferation of technology. Intellectual property protection is a key factor for economic growth and advancement in the high technology sector. This book discusses the intangible nature of intellectual property and the worldwide inconsistency of standard practices.